2011
DOI: 10.1007/s10915-010-9453-3
|View full text |Cite
|
Sign up to set email alerts
|

Adaptivity and a Posteriori Error Control for Bifurcation Problems II: Incompressible Fluid Flow in Open Systems with Z 2 Symmetry

Abstract: Access from the University of Nottingham repository:http://eprints.nottingham.ac.uk/1257/1/cliffe_et_al_z2_bifurcation.pdf Copyright and reuse:The Nottingham ePrints service makes this work by researchers of the University of Nottingham available open access under the following conditions. This article is made available under the University of Nottingham End User licence and may be reused according to the conditions of the licence. For more details see: http://eprints.nottingham.ac.uk/end_user_agreement.pdf A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…For this reason DWR has been already used in many fields. For example in [22] DWR has been used to accurately compute the lift and drag of wing profile, moreover in [23,24] DWR has been used to accurately compute eigenvalues of eigenvalue problems from different areas of physics.…”
Section: Dual Weighted Residual a Posteriori Error Estimatormentioning
confidence: 99%
“…For this reason DWR has been already used in many fields. For example in [22] DWR has been used to accurately compute the lift and drag of wing profile, moreover in [23,24] DWR has been used to accurately compute eigenvalues of eigenvalue problems from different areas of physics.…”
Section: Dual Weighted Residual a Posteriori Error Estimatormentioning
confidence: 99%
“…To this end, we are interested in numerically estimating the critical Reynolds number Re, at which a (pitchfork) bifurcation point first occurs; a review of techniques for bifurcation detection can be found in Cliffe et al [13], for example. The work in this article expands upon our recent work in [12] and [10] to include problems whose geometries exhibit both rotational and reflectional symmetry. The detection of bifurcation points in this setting is now well understood, for example, see Golubitsky and Schaeffer [19].…”
mentioning
confidence: 98%
“…also [10]. In contrast, flow through a cylindrical pipe with a sudden expansion remains poorly understood.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerical experiments presented in both one-and two-dimensions clearly highlight the practical performance of the proposed a posteriori error indicator within an automatic adaptive mesh refinement strategy. The extension of these ideas to more complex problems involving incompressible fluid flows in open systems will be considered in the companion articles [11,12].…”
mentioning
confidence: 99%